Bovine Derived in vitro Cultures Generate Heterogeneous Populations of Antigen Presenting Cells - Guzman, Efrain; Pujol, Myriam; Ribeca, Paolo; Montoya, Maria (Frontiers in Immunology, 2019)
Antigen presenting cells (APC) of the mononuclear phagocytic system include dendritic cells (DCs) and macrophages (Macs) which are essential mediators of innate and adaptive immune responses. Many of the biological functions attributed to these cell subsets have been elucidated using models that utilize in vitro-matured cells derived from common progenitors. However, it has recently been shown that monocyte culture systems generate heterogeneous populations of cells, DCs and Macs. In light of these findings, we analysed the most commonly used bovine in vitro-derived APC models and compared them to bona fide DCs and Macs. Here, we show that bovine monocyte-derived DCs and Macs can be differentiated on the basis of CD11c and MHC class II (MHCII) expression and that in vitro conditions generate a heterologous group of both DCs and Macs with defined and specific biological activities. In addition, skin-migrating macrophages present in the bovine afferent lymph were identified and phenotyped for the first time. RNA sequencing analyses showed that these monophagocytic cells have distinct transcriptomic profiles similar to those described in other species. These results have important implications for the interpretation of data obtained using in vitro systems.